1983
DOI: 10.1177/000331978303400108
|View full text |Cite
|
Sign up to set email alerts
|

The Success Rate of Fibrinolytic Therapy in Fresh and Old Thrombosis of the Iliac and Femoral Veins

Abstract: Since it is still a wide-held belief that fibrinolytic therapy can clear thrombi from deep veins only while they are fresh, we retrospectively analyzed the phlebographic results obtained in 85 patients with thrombosis of the iliac and/or femoral veins with symptoms present for 1 day to 8 weeks prior to treatment. Streptokinase, urokinase, or both drugs successively were administered in these patients for a mean of 9 days (range: 2 to 26 days). Complete or partial resolution of the thrombotic occlusion was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…In other words, rt-PA + H proved effective up to 14 days after embolization, and fibrinolytic therapy may prove useful even after a lon ger period of time. Clinical experience seems to confirm our results; indeed, in clinical trials, one of the suggested criteria for the enrollment of patients for thrombolytic therapy was the onset of symptoms of PE within the past 14 days [1][2][3][4][15][16][17][18], On the contrary, in patients treated with H alone, a significant inverse correlation between the putative age of the emboli and the extent of perfusion or standard PaCT improvement 1 week after the beginning of treatment shows the smaller effectiveness of H in old pulmonary emboli. This can be explained by the lack of direct fibrinolytic activity of H [19]; accordingly, the emboli are lysed only by the endogenous fibrinolytic sys tem.…”
Section: Discussionsupporting
confidence: 60%
“…In other words, rt-PA + H proved effective up to 14 days after embolization, and fibrinolytic therapy may prove useful even after a lon ger period of time. Clinical experience seems to confirm our results; indeed, in clinical trials, one of the suggested criteria for the enrollment of patients for thrombolytic therapy was the onset of symptoms of PE within the past 14 days [1][2][3][4][15][16][17][18], On the contrary, in patients treated with H alone, a significant inverse correlation between the putative age of the emboli and the extent of perfusion or standard PaCT improvement 1 week after the beginning of treatment shows the smaller effectiveness of H in old pulmonary emboli. This can be explained by the lack of direct fibrinolytic activity of H [19]; accordingly, the emboli are lysed only by the endogenous fibrinolytic sys tem.…”
Section: Discussionsupporting
confidence: 60%
“…The findings demonstrated that thrombolytic therapy is more effective in thromboses that are acute or less than 4 weeks old. 17 It remains unclear whether or not to use IVC filters in patients with extensive DVT who are undergoing thrombolysis. Pulmonary emboli can occur with catheter-directed manipulation; however, these emboli are usually small and are not of clinical significance.…”
Section: Treatment Of Acute Deep Venous Thrombosismentioning
confidence: 99%
“…This therapy is most likely to be successful when thrombus is acute (<14 days old) and much less effective when the clot is chronic (>4 weeks old). 2 Such accelerated pharmacological thrombolysis may be performed even with a reduced dose of lytic agent associated with a lower overall duration of infusion. Various lytic agents can be chosen based on their individual biological half life, fibrin affinity and specificity, time to clot lysis, and respective dosing.…”
Section: Catheter-directed Thrombolysismentioning
confidence: 99%